PENERAPAN TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN DAYA SAING UMKM BATIK DESA GUNTING - Dermayanti, Kiki; Sukamto; M Dayat (Journal of Islamic Economics (JoIE), 2024)
Introduction: The increasingly competitive development of Indonesia's economy has intensified competition in the business world. Total Quality Management (TQM) has become a popular approach across various industries, including Micro, Small, and Medium Enterprises (MSMEs). This research focuses on MSMEs, aiming to investigate how TQM is implemented to enhance competitiveness. TQM is a management approach that prioritizes quality as a key business strategy, emphasizing customer satisfaction and engaging all employees in the process to increase competitiveness. This study highlights the implementation of TQM by Batik MSMEs in Pajaran, Gunting village, Sukorejo district, Pasuruan regency, which includes improving product quality, production process efficiency, employee training, and customer engagement. Research Methods: The research employs a qualitative approach with a descriptive method, including observation, interviews, and documentation. Results: The findings indicate that the implementation of TQM has had a significant positive impact on the competitiveness of Batik MSMEs, particularly in terms of improving product quality, customer satisfaction, and operational efficiency. Conclusion: The study underscores the importance of implementing TQM as a strategy to increase competitiveness in an increasingly competitive market. It is recommended that other MSMEs consider adopting TQM to achieve long term and sustainable success.